Hábitat y Cosmogonía del pueblo Wayúu (2021)
The indigenous capital of Colombia, Uribia, is the largest municipality of La Guajira, hosting the largest number of indigenous people of the Wayúu ethnicity, being their main human population, spread throughout the territory in Rancherías and some located in the urban area; their concepts and ways of seeing the world around them is ancestral and transcends the thought of the Alijuunas. The language, cosmology, social hierarchy, economy, housing, arts, games, territory and space are some of their main cultural bases, bases very present today for these semi-nomadic people, even in spite of the cultural differences they present with the Alijuunas. This research focuses mainly on the culture of the region of Uribia, evaluating the situation of the urban panorama of this territory in contrast to the life of the Wayúu and how they live in their natural habitat, which is their ranchería, the current state of Wayúu and Alijuna relations, and how the interaction of these has affected both parties, perceiving a cultural and patrimonial detriment due to governmental forgetfulness, which more than helping has forgotten and attacked the region with harmful policies.